Review: Evaluasi Kepatuhan Pasien Terhadap Penggunaan Obat Antihipertensi Di Rumah Sakit Dan Puskesmas - Maulidya Rachma Az Zahra; Bella Fevi Aristia; Alfu Laila; Eka Putri Nurhidayah (CV. ITTC INDONESIA, 2025)
Hypertension is a condition of persistent blood pressure above normal (≥140/90 mmHg) that affects 1.28 billion adults globally, with an increasing prevalence in developing countries including Indonesia (34.1% in 2018). The purpose of this review article is to determine the level of patient compliance in the use of antihypertensive drugs in hospitals and health centers. The method used is a narrative literature review by searching 9 articles published between 2020 and 2025. The literature review search was conducted through academic databases from Google Scholar, ResearchGate, and ScienceDirect. The selected articles must be relevant to the topic of patient compliance in the use of antihypertensive drugs and meet the predetermined inclusion criteria. The results showed that the level of patient compliance varied, with most patients showing moderate compliance. Several factors that influence patient compliance include the number of drugs consumed and the duration of treatment. Through this review, it is hoped that it can improve readers' understanding in order to improve the level of patient compliance in undergoing hypertension therapy.